Dampak Kenaikan Harga Pupuk terhadap Produktifitas Kelapa Sawit Kabupaten Pelalawan - Putra Fadli Harahap; Syaiful Hadi; Rosnita Rosnita (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research was conducted at independent oil palm farming in Pelalawan Regency, which was motivated by complaints from oil palm farmers about increasing the price of fertilizer. Therefore, this study aims to analyze fertilizer use before and after increasing the price and the survey method and the researcher interviewed eighty respondents based on questionnaires. The multistage sampling sampling takes four sub-districts with the largest area of oil palm plantation in Pelalawan Regency. The analyzing data with paired sample t-tests aims to compare fertilizer and herbicide usage before and after a price increase. The research showed fertilizer use before the price increase was 1.417,46 Kg/Ha/Year, whereas after the rise was 1.105,39 Kg/Ha/Year. Whereas the productivity of oil palm before the price increase was 20.029.15 Kg/Ha/Year, and after the price increase was 17.769.38 Kg/Ha/Year.